Oral Tradition in African Literature - Ce, Chinenye; Smith, Charles (Book collections on Project MUSE., 2015)
This study of oral tradition in African literature is borne from the awareness that African verbal arts still survive in works of discerning writers and in the conscious exploration of its tropes, perspectives, philosophy and consciousness, its complementary realism, and ontology, for the delineation of authentic African response to memory, history and other possible comparisons with modern existence such as witnessed in recent developments of the African novel. In this series we have strived to adopt innovative and multilayered perspectives on orality or indigeneity and its manifestations on contemporary African and new literatures. These studies use multi-faceted theories of orality which discuss and deconstruct notions of history, truth-claims and identity-making, not excluding gender and genealogy (cultural and biological) studies in African contexts.